ANALYSIS OF THE INVESTMENT CLIMATE OF DENMARK - Elvina Lymonova; Marina V. Filchenkova (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
The investment climate is a key factor for attracting capital, stimulating innovation and strengthening competitiveness. The purpose of the study is to analyze the current state of the investment environment in the country, assess its attractiveness for foreign investors, and reveal the main factors affecting the development of business in Denmark as one of the leading countries of the European Union. The analysis of the investment attractiveness of the country is based on the research of available data, official reports and other sources of information. A general overview of the current investment climate in Denmark indicates that the country continues to be an attractive destination for investors. The country is known for its stable economy, high level of innovation and strong legal system, which creates a favorable environment for investment. The article carried out a thorough analysis of not only the main macroeconomic indicators, but also a comparative analysis of investor protection, analyzed the dynamics of the corruption perception index, the level of education among the country’s population, and analyzed the innovative environment of Denmark. In addition, the article discusses the types of risk for investing in the Danish economy. Denmark’s successful competitiveness is due to a combination of several factors: emphasis on innovation and research, high quality education, flexible labor market, efficient infrastructure, state support for entrepreneurship and a stable political and economic situation. The results of the study provide concrete recommendations for government and business, promoting investment attraction and sustainable economic growth in Denmark. The country has significant potential for further development of its investment climate thanks to numerous advantages, in particular in the fields of green energy and information technology. Denmark is pursuing an energy efficiency policy and phasing out fossil fuels, as well as investing in digital infrastructure. However, there are certain risks, such as political and legislative changes, geopolitical factors, changes in international trade and market competition, which may affect investment activities in the country. Investors need to carefully analyze these risks and take them into account in their risk management strategies.